Estudo in vitro da efetividade do hidróxido de cálcio e da polimixina B na eliminação das endotoxinas presentes nos canais radiculares - Oliveira, Luciane Dias de [UNESP] (2002)
The cell walls of Gram-negatives bacteria contain a lipopolysaccharide complex, also called endotoxin, which may be released into the environment as blebs during bacterial cell growth or as large pieces of membrane upon cell death. Endotoxins are potent agents capable of initiating various biological responses, which include initiation of osteoclastic activity and subsequent bane resorption. The purpose of this study was to evaluate the effectiveness of intracanal medicaments in the elimination of the endotoxins in the root canal. Seventy-fivefreshly extracted, single-rooted, straight human anterior teeth were used in the study. The crowns were removed and the apex cut in 3mm, standardizing the size of the specimens in 14mm. The root canals of the teeth were instrumented, and the roots apex hindered with light-cure resin. The specimens were sterilized and it was inoculated endotoxin of Escherichia coli inside sixty root canals. The teeth were divided in 5 experimental groups (15 teeth). The group 1 received as intracanal medicament the paste of calcium hydroxide, the group 2 received a solution contends Polymyxin B pure, the group 3 received a solution contends Polymyxin 8, neomycin sulfate and hydrocortisone, the group 4 (control positive) didn't receive any medicament and in the group 5 (controls negative) the endotoxin was not inoculated. The teeth were maintained in stove to a temperature of 37±1ºC and relative humidity 100% for 7 days. Alter this period, the neutralization of the endotoxin was verified being used Limulus lisate and the production of antibodies in lymphocyte B culture. The results obtained with the Limulus lisate were submitted to the statistical analysis using the test of MannWhitney and was verified that the treatments with the calcium hydroxide and with the Polymyxin B pure went effective in to neutralization of the endotoxin in the root canals. The results obtained in the lymphocyte...